Determination of Active Personal Space Based on Emotion when Interacting with a Service Robot. (18th March 2013) - Banik, Sajal Chandra; Gupta, Ashoke Kumar Sen; Habib, M. K.; Mousumi, R. N.
This paper focuses on the determination of active personal space (APS) for a service robot based on emotional status. This is required for human-robot interaction at ease. Here, APS means the active distance (relative distance during interaction and action) between the robot and the human. APS is a function of emotion both in the human and in the robot. The other factors which are considered here are age, height, familiarity with robot, and relative motion between robot and human. According to these factors, the changes in APS are shown with graphs. During the experiments two robot emotions are considered: normal and angry. The causes of variation of APS based on the two modes are also explained.